Identification of inhibitors for the transmembrane Trypanosoma cruzi eIF2α kinase relevant for parasite proliferation - Marcelino, Tiago de Paula; Fala, Angela Maria; da Silva, Matheus Monteiro; Souza-Melo, Normanda; Malvezzi, Amaranta Muniz; Klippel, Angélica Hollunder; Zoltner, Martin; Padilla-Mejia, Norma; Kosto, Samantha; Field, Mark C; Burle-Caldas, Gabriela de Assis; Teixeira, Santuza Maria Ribeiro; et al. (The Journal of biological chemistry, 2023)
The TcK2 protein kinase of Trypanosoma cruzi, the causative agent of Chagas disease, is structurally similar to the human kinase PERK, which phosphorylates the initiation factor eIF2α and, in turn, inhibits translation initiation. We have previously shown that absence of TcK2 kinase impairs parasite proliferation within mammalian cells, positioning it as a potential target for treatment of Chagas disease. To better understand its role in the parasite, here we initially confirmed the importance of TcK2 in parasite proliferation by generating CRISPR/Cas9 TcK2-null cells, albeit they more efficiently differentiate into infective forms. Proteomics indicates that the TcK2 knockout of proliferative forms expresses proteins including trans-sialidases, normally restricted to infective and nonproliferative trypomastigotes explaining decreased proliferation and better differentiation. TcK2 knockout cells lost phosphorylation of eukaryotic initiation factor 3 and cyclic AMP responsive-like element, recognized to promote growth, likely explaining both decreased proliferation and augmented differentiation. To identify specific inhibitors, a library of 379 kinase inhibitors was screened by differential scanning fluorimetry using a recombinant TcK2 encompassing the kinase domain and selected molecules were tested for kinase inhibition. Only Dasatinib and PF-477736, inhibitors of Src/Abl and ChK1 kinases, showed inhibitory activity with IC50 of 0.2 ± 0.02 mM and 0.8 ± 0.1, respectively. In infected cells Dasatinib inhibited growth of parental amastigotes (IC50 = 0.6 ± 0.2 mM) but not TcK2 of depleted parasites (IC50 > 34 mM) identifying Dasatinib as a potential lead for development of therapeutics for Chagas disease targeting TcK2.
Keywords: Chagasova nemoc; Animals; Dasatinib; Mammals; proteome; proliferace buněk; paraziti; protein kinase; lidé; eIF-2 Kinase; dasatinib; Parasites; recombinant protein; savci; eIF2α; chagas disease; invasion; chemical inhibitor; Cell Proliferation; Chagas Disease; T.cruzi EIF2AK2; zvířata; kinasa eIF-2; Trypanosoma cruzi; Humans